(8xy-y)(8xy-y)=

Simple and best practice solution for (8xy-y)(8xy-y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8xy-y)(8xy-y)= equation:


Simplifying
(8xy + -1y)(8xy + -1y) = 0

Multiply (8xy + -1y) * (8xy + -1y)
(8xy * (8xy + -1y) + -1y * (8xy + -1y)) = 0
((8xy * 8xy + -1y * 8xy) + -1y * (8xy + -1y)) = 0

Reorder the terms:
((-8xy2 + 64x2y2) + -1y * (8xy + -1y)) = 0
((-8xy2 + 64x2y2) + -1y * (8xy + -1y)) = 0
(-8xy2 + 64x2y2 + (8xy * -1y + -1y * -1y)) = 0
(-8xy2 + 64x2y2 + (-8xy2 + 1y2)) = 0

Reorder the terms:
(-8xy2 + -8xy2 + 64x2y2 + 1y2) = 0

Combine like terms: -8xy2 + -8xy2 = -16xy2
(-16xy2 + 64x2y2 + 1y2) = 0

Solving
-16xy2 + 64x2y2 + 1y2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'y2'.
y2(-16x + 64x2 + 1) = 0

Factor a trinomial.
y2((8x + -1)(8x + -1)) = 0

Subproblem 1

Set the factor 'y2' equal to zero and attempt to solve: Simplifying y2 = 0 Solving y2 = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y2' to each side of the equation. y2 + -1y2 = 0 + -1y2 Remove the zero: 0 = -1y2 Simplifying 0 = -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(8x + -1)' equal to zero and attempt to solve: Simplifying 8x + -1 = 0 Reorder the terms: -1 + 8x = 0 Solving -1 + 8x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 8x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 8x = 0 + 1 8x = 0 + 1 Combine like terms: 0 + 1 = 1 8x = 1 Divide each side by '8'. x = 0.125 Simplifying x = 0.125

Subproblem 3

Set the factor '(8x + -1)' equal to zero and attempt to solve: Simplifying 8x + -1 = 0 Reorder the terms: -1 + 8x = 0 Solving -1 + 8x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 8x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 8x = 0 + 1 8x = 0 + 1 Combine like terms: 0 + 1 = 1 8x = 1 Divide each side by '8'. x = 0.125 Simplifying x = 0.125

Solution

x = {0.125, 0.125}

See similar equations:

| 7y-10(6y-13)=77 | | 4x-24=-30+6x | | 11x+3=5x+27 | | -8=2n+2n | | 2y+7-22y= | | -7.97(-5+a)=56.586 | | 7(-6)+8y=-18 | | 5.66-12.9p-5.59=-12.7p+2.97 | | 7x+8(9x+57)=-18 | | 44/8.75 | | -4/(x^2-4)=0 | | 2x+(x+3)/6=4 | | 1/7(x-10)=7 | | 38.25=4.5(6.4+x) | | 3.2c-18.2c+13.27=-15.7c+10.05 | | 3x^2=x-1 | | 5(2x-8)=1/5(30+60) | | -99.999=-5.6x-7.6 | | 6-10/11x=16 | | 24=10-3x | | -6(-3+7x)=144 | | 7(-14)[3(-7)-5(-4)]= | | 9b-17-13b=-17-11b | | 8.75/44 | | ((e^11x)-1)/x | | p+2/8=3/9 | | 12s-17=-13+15s-10 | | x-3/3=x-4/4 | | 19j-8=3+20j+9 | | x-0.5+20=37 | | 2x+3+x+7=90 | | -3(7+x)+8=-3(x+7) |

Equations solver categories